GEOCHEMICAL CHARACTERISTICS OF ACIDIC DIKE SWARM FROM THE EASTERN SEGMENT OF THE ERTIX TECTONIC BELT, ALTAI OROGENY AND ITS GEOLOGICAL IMPLICATIONS - Gong H.L.; Chen Z.L.; Li L.; Hu Y.Q.; Lai X.R.; Ma Q.Y.; Li Y.Y.; Hu B.; Zhang W.G. (My University, 2007)
Field investigation revealed series of undeformed acidic dike swarm developed between the Ertix active fault and the Fuyun-Xibodu fault in the eastern segment of the Ertix tectonic belt, southern Altai orogeny, where Hercynian gneissic granites and the Upper Carboniferous Ertix Formation outcropped. The content of SiO2 in the dike is 70.9% - 75.38%, and that of K2 O + Na2 O is 7.55% - 8.99%. For most of samples, the content of Na is larger than that of K. The Rittmann index (δ) varies from 1.8 to 2.5. The content of Al2O3, equals to 12.8% - 14.53%. The value of A/ CNK is 0.9 - 1.1, and that of NK/A ranges from 0.7 to 0.9, suggesting that the dike should be attributed to A-type granitoids and sub-alkaline rock with metaluminous-low peraluminous character and lower Magnesium, higher Kalium and Natrium, lower Calcium and Strontium, and higher (Fe/Mg)mol. Analyses of trace and rare earth elements showed that these rocks are rich of light rare earth elements and relatively rich of great ion lithophile elements with obviously middle minus-Eu abnormity, indicating obviously fountainhead of crust resource. The U-Pb dating of zircon by Second Ion Microprobe revealed that the dike formed between 277 - 286Ma. Therefore, it was suggested that acidic dike swarm resulted from the partial melting of crustal material in regional extensional surrounding after the end of the Hercynian Altai orogenesis.
Keywords: A-TYPE GRANITOIDS; ACIDIC DIKE SWARM; ALTAI OROGENY; ERTIX TECTONIC BELT; GEOCHEMISTRY